Introduction to Health Care, 5th Edition - Lee Haroun (Cengage Learning, 2020)
Preparing you for real-world practice, Haroun/Mitchell's INTRODUCTION TO HEALTH CARE, Fifth Edition, provides an easy-to-read introduction to the foundational skills necessary for a range of health care professions. Emphasizing core health care competencies -- communication, infection control and professionalism -- the text delivers thorough coverage of both the soft skills and basic clinical skills needed by those entering health care training programs or considering a career in health care. Its unique five-step problem-solving model helps you "think like a health care professional" and sharpen your critical thinking skills, while numerous hands-on activities enable you to put chapter concept into practice. Completely up to date, it reflects the latest research and includes expansive coverage of such emerging issues as the opioid crisis, precision/personalized medicine, suicide prevention, health disparities, patient rights and much more. Also available: MindTap digital learning solution.